Transcriptome analysis of the two unrelated fungal β-lactam producers Acremonium chrysogenum and Penicillium chrysogenum: Velvet-regulated genes are major targets during conventional strain improvement programs - Terfehr, Dominik (BMC Genomics, 2017)
BACKGROUND: Cephalosporins and penicillins are the most frequently used β-lactam antibiotics for the treatment of human infections worldwide. The main industrial producers of these antibiotics are Acremonium chrysogenum and Penicillium chrysogenum, two taxonomically unrelated fungi. Both were subjects of long-term strain development programs to reach economically relevant antibiotic titers. It is so far unknown, whether equivalent changes in gene expression lead to elevated antibiotic titers in production strains. RESULTS: Using the sequence of PcbC, a key enzyme of β-lactam antibiotic biosynthesis, from eighteen different pro- and eukaryotic microorganisms, we have constructed a phylogenetic tree to demonstrate the distant relationship of both fungal producers. To address the question whether both fungi have undergone similar genetic adaptions, we have performed a comparative gene expression analysis of wild-type and production strains. We found that strain improvement is associated with the remodeling of the transcriptional landscape in both fungi. In P. chrysogenum, 748 genes showed differential expression, while 1572 genes from A. chrysogenum are differentially expressed in the industrial strain. Common in both fungi is the upregulation of genes belonging to primary and secondary metabolism, notably those involved in precursor supply for β-lactam production. Other genes not essential for β-lactam production are downregulated with a preference for those responsible for transport processes or biosynthesis of other secondary metabolites. Transcriptional regulation was shown to be an important parameter during strain improvement in different organisms. We therefore investigated deletion strains of the major transcriptional regulator velvet from both production strains. We identified 567 P. chrysogenum and 412 A. chrysogenum Velvet target genes. In both deletion strains, approximately 50% of all secondary metabolite cluster genes are differentially regulated, including β-lactam biosynthesis genes. Most importantly, 35-57% of Velvet target genes are among those that showed differential expression in both improved industrial strains. CONCLUSIONS: The major finding of our comparative transcriptome analysis is that strain improvement programs in two unrelated fungal β-lactam antibiotic producers alter the expression of target genes of Velvet, a global regulator of secondary metabolism. From these results, we conclude that regulatory alterations are crucial contributing factors for improved β-lactam antibiotic titers during strain improvement in both fungi. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12864-017-3663-0) contains supplementary material, which is available to authorized users.